Paradoxos da maternidade: a recontextualização do ideal materno no Instagram - Maia, Camila Moreira (2023)
This work is located in the area of Critical Social Psychology and aims to perform a discourse analysis of posts about motherhood on Instagram. It is intended to understand the implications of living in networks in the forms of representation and social interaction in the context of motherhood. Motherhood is seen here as a biopsychosocial phenomenon that adds questions related to the biological changes that occur in the woman's body, but also to the meanings offered by the culture for the understanding of this female condition. We emphasize the notion of maternal ideal, an ideology constructed from the end of the 19th century, within the formation of the traditional bourgeois family, to justify the engagement of women in the role of mother, through scientific, religious, philosophical and political discourses. These discourses have been strongly influenced by technological, economic and sociocultural transformations. Special emphasis is placed on the criticisms made by Feminisms, by Gender Studies and by Mother Studies; and the impacts of reproductive technologies and changes in conjugality and family models during the 20th century. The media has always played an important role in reinforcing or combating patterns of motherhood. Therefore, the history of the relationship between motherhood and the media is explored, emphasizing the characteristics of a Culture of Connectivity based, above all, on informational capitalism and on values such as visibility and popularity; and responsible for blurring the boundaries between public and private. It is interesting to know how this culture interacts with maternal issues in the production of discourses and interactions in social networks. The theoretical-methodological perspective used is the Critical Discourse Analysis, especially in the versions of the Anglo-Saxon School. This approach understands that social transformations are partially discursive, so it proposes a discourse analysis model for identifying processes of change or social reproduction. As a methodological path, it initially suggests the identification of a discursive problem and the description of its relationship with the other elements of social practice, through an ethnographic approach. Then, we move on to the analysis of discourse itself, carried out here through the strategies developed by Fairclough and Chouliaraki (1999) for the appreciation of texts and by Kress and Van Leeuwen (2006) for the appreciation of images. As a result, we identified that the maternal ideal has been recontextualized on Instagram based on three main discursive trends. The first would be that of reproduction, since traditional narratives about motherhood continue to be reproduced through hybrid discourses that unite scientific, pedagogical and moral genres with discursive genres characteristic of the internet. The second would be a critique of the maternal ideal, insofar as they denounce the illusory and subjugating character of these models of motherhood and which point to the contestation of a patriarchal society that has historically enshrined ideological discourses aimed at keeping women in a subordinate position. Finally, the third trend is the transformation of this ideal, because today mothers can narrate their experiences in a network, reformulating patriarchal discourses and can disseminate the discourse of a less exhausting and more possible motherhood.